Predictors of intrahepatic cholangiocarcinoma recurrence after surgical treatment - E. V. Kondratyev; A. D. Smirnova; G. G. Karmazanovsky; A. S. Tyan; N. N. Britskaya; M. G. Efanov; B. N. Gurmikov (Исследования и практика в медицине)
Purpose of the study. To study the CT semiotics of intrahepatic cholangiocarcinoma (ICC) to determine the prognostic markers of recurrence. To analyze the association between CT characteristics of ICC and mutations in IDH1/2, MET, KRAS, BRAF, ERBB2, EGFR, FGFR genes.Materials and methods. We analyzed databases and diagnostic images of Vishnevsky National Medical Research Center of Surgery and Loginov Moscow Clinical Research Center for the period from April 2016 to January 2022 using the key queries «intrahepatic cholangiocarcinoma», «liver», «hepatocellular carcinoma», «metastases», «radio genomics». 142 patients with liver neoplasms were identified, including 90 cases of ICC, 31 cases of hepatocellular carcinoma and 21 cases of metastatic liver lesions, all morphologically verified (histologic and immunohistochemical analysis of biopsy material).Results. Associations between CT features and mutations of MET and IDH1/2 genes were determined. According to the results of statistical analysis all four CT-signs, such as bile duct dilatation, capsule retraction, presence of dropout foci and tissue volume changes, are correlated with the probability of recurrence (death) in patients with ICC.Conclusion. In a retrospective study, our results emphasize the potential prognostic significance of CT signs of ICC. We identified CT signs that allow differential diagnosis of ICC with hepatocellular carcinoma and colorectal cancer metastases. We also identified associations between CT signs of ICC and mutations of IDH1/2 and MET genes, which may allow us to non-invasively obtain data on clinically significant molecular markers of tumors to apply a personalized approach to patient treatment.